A new dendrobatid frog (Anura: Dendrobatidae: Anomaloglossus) from the Orinoquian rainforest, southern Venezuela - Barrio-Amorós, César L.; Santos, Juan Carlos; Jovanovic, Olga (Zootaxa, 2010)
A new species of Anomaloglossus is described from the Venezuelan Guayana; it is the 21 st described species of Anomaloglossus from the Guiana Shield, and the 15 th from Venezuela. This species inhabits rainforest on granitic substrate on the northwestern edge of the Guiana Shield (Estado Amazonas, Venezuela). The new species is distinguished from congeners by sexual dimorphism, its unique male color pattern (including two bright orange parotoid marks and two orange paracloacal spots on dark brown background), call characteristics and other morphological features. Though to the new species is known only from the northwestern edge of the Guiana Shield, its distribution may be more extensive, as there are no significant biogeographic barriers isolating the type locality from the granitic lowlands of Venezuela.